2016
DOI: 10.1017/sjp.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation Scale: Adaptation to Spanish

Abstract: Entrepreneurship is linked to the perception of opportunities, to orientation, to attitudes, to the fear of failure and to entrepreneurial motivations. Entrepreneurial orientation is a fundamental construct for understanding the phenomenon of entrepreneurship. What is more, it is multidimensional and has attracted considerable attention from researchers in recent years. The objective of this study was to adapt the original 12-item English scale to Spanish and to analyze its psychometric properties. The partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Adapted to Spanish by Boada-Grau et al (2016) on the basis of its original version, developed by Lee et al (2011) , it is a Likert-type scale that, based on 12 items, measures the degree of agreement or disagreement on different levels (on a scale of 1–5, with 1 = completely disagree, and 5 = completely agree). These assess entrepreneurial orientation in four sub-dimensions: autonomy (related to self-sufficiency in facing challenges), innovation (related to enjoyment and orientation to work on new things), risk-taking (related to the willingness to face difficulties in the future), and aggressive competitiveness (related to perseverance and belief in success).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted to Spanish by Boada-Grau et al (2016) on the basis of its original version, developed by Lee et al (2011) , it is a Likert-type scale that, based on 12 items, measures the degree of agreement or disagreement on different levels (on a scale of 1–5, with 1 = completely disagree, and 5 = completely agree). These assess entrepreneurial orientation in four sub-dimensions: autonomy (related to self-sufficiency in facing challenges), innovation (related to enjoyment and orientation to work on new things), risk-taking (related to the willingness to face difficulties in the future), and aggressive competitiveness (related to perseverance and belief in success).…”
Section: Methodsmentioning
confidence: 99%
“…These assess entrepreneurial orientation in four sub-dimensions: autonomy (related to self-sufficiency in facing challenges), innovation (related to enjoyment and orientation to work on new things), risk-taking (related to the willingness to face difficulties in the future), and aggressive competitiveness (related to perseverance and belief in success). Examples of sentences considered in the items are “I do not want to be financially supported by my parents, family, etc., because I am already an adult,” “I am more interested in starting my own business than in getting a job,” and “even if I start new businesses and fail many times, I will keep trying until I succeed.” According to Boada-Grau et al (2016) , the instrument had good psychometric properties, both in terms of validity and reliability. In this study, the overall reliability of the instrument, as shown by its Cronbach’s Alpha, was 0.74.…”
Section: Methodsmentioning
confidence: 99%
“…Adapted to Spanish by Boada-Grau et al (2016) based on its original version, developed by Lee et al (2011) , it is a Likert-type scale with 12 items. The scale measures the degree of agreement or disagreement on different levels (on a scale of one to five, with 1 = completely disagree, and 5 = completely agree).…”
Section: Methodsmentioning
confidence: 99%
“…Examples of sentences considered in the items are "I don't want to be financially supported by my parents, family, etc., because I am already an adult, " "I am more interested in starting my own business than in getting a job, " and "even if I start new businesses and fail many times, I will keep trying until I succeed." According to Boada-Grau et al (2016) the instrument had good psychometric properties, both in terms of validity and reliability. In this study, the overall reliability of the instrument, as shown by its Cronbach's Alpha, was 0.74.…”
Section: Entrepreneurial Orientation Scalementioning
confidence: 99%
“…El fomento del emprendimiento, particularmente en la población escolar juvenil, ha suscitado un alto interés por la creación de instrumentos que midan el impacto de los programas formativos (Athayde, 2012(Athayde, , 2009Bernal-Guerrero et al, 2020;Chang y Rieple, 2013;Draycott et al, 2011;Hodzic, 2016;Lackéus y Sävetun, 2018;Liguori et al, 2019;Man, 2006;Pepin y St-Jean, 2019). Es evidente el interés por la operatividad métrica de la personalidad y el potencial emprendedor: Santos et al (2014) idearon el Entrepreneurial Potential Assessment Inventory (EPAI), conformado por cuatro dimensiones fundamentales, divididas en once subdimensiones; Muñiz et al (2014) propusieron, asimismo, la Battery for the Assessment of the Enterprising Personality (BEPE), que evalúa los ocho rasgos de personalidad específicos identificados en la literatura como más idóneos para la descripción de la personalidad emprendedora; Boada-Grau et al (2016) adaptaron al español la Entrepreneurial Attitude Orientation Scale (EAO) de Robinson et al (1991). Athayde (2009) El ATE se ha validado en varios países, entre ellos, Reino Unido, Italia y Sudáfrica (tabla 1) (Athayde, 2009;Spagnoli et al, 2017;Steenekamp et al, 2011), pero no se ha validado en España.…”
Section: Introductionunclassified